THE CITIZEN AS OBJECT AND SUBJECT OF THE STATE’S SECURITY POLICY - Gheorghe COSTACHI (Legea și Viața)
One of the fundamental objectives of the state’s security policy is the protection of the citizen and their rights. The theoretical significance of this subject arises from the essential value of the citizen in a rule of law state, where the citizen represents a pillar of the state’s resilience and plays a crucial role in its consolidation. From this perspective, it becomes evident that the citizen should not be viewed only as an object of protection through security policy, but also as an active actor in the process of formulating and implementing this policy. The purpose of this study is to clarify the role of the citizen both as the subject of protection within the security policy and as an active participant, with a significant impact on the development and application of security measures. The approach to this topic holds both theoretical and practical value: on one hand, it will contribute to deepening the theory of security in a rule of law state, while on the other hand, through a detailed analysis of the key aspects of security policy, it will facilitate the identification of effective solutions for its improvement. In line with the study’s objectives, it will be structured into two sections: the first will analyze the role of the citizen as the subject of the security policy, and the second will examine their active involvement in the development and implementation of this policy.